It's our research : getting stakeholder buy-in for user experience research projects - Sharon, Tomer (Morgan Kaufmann, 2012)
It's Our Research provides a strategic framework for people who practice UX research who wish to be heard by their stakeholders. It gives you the techniques needed to involve stakeholders throughout the process of planning, execution, analysis, and reporting UX research. Dramatically increase the chances that product managers, engineers, and management agree to do research and act upon its results; follow Tomer Sharon's techniques and methods detailed inside. *Features a series of video interviews with UX practitioners and researchers *Provides dozens of case studies and visuals from international research practitioners *Provides a toolset that will help you justify your work to stakeholders, deal with office politics, and hone your client skills *Presents tried and tested techniques for working to reach positive, useful, and fruitful outcomes.